Development of Nursing Service System for Critical Ill Patients, Mahasarakham Hospital Network - Narthasilpa, Putthakunya; Taiwong, Anucha; Promso, Nalinrat; Junkami, Aungkana; Sinoo, Parichat; Sansi, Nissama; Ponjantao, Kanchana; Waiyapat, Yuwadee (Princess of Naradhiwas University Journal, 2025)
This research and development aimed to develop and evaluate the implementation of a Critical Care Nursing Service System in the Mahasarakham Hospital Network. The study consisted of 4 phases: 1) situation analysis, problem identification, and needs assessment; 2) development of the critical care nursing service system, quality verification, and pilot study; 3) implementation of the critical care nursing service system to examine its effectiveness with 240 critical patients and 116 professional nurses, and 4) evaluation, improvement, and system quality confirmation. Research instruments included in-depth interview forms, nursing outcome records, critical care nursing service system structure assessment forms, knowledge tests, nursing practice evaluation forms, satisfaction assessment forms, and focus group discussion guidelines. Five experts validated all instruments. The research was conducted between October 2022 and April 2024. Data were analyzed using descriptive statistics, chi-square test, and content analysis. The results showed that the developed critical care nursing service system aligned with the context and practitioners' needs, comprising 3 aspects: 1) Structure, including policies, facilities, personnel, and medical equipment; 2) Process, including professional nurse competency development in critical care units, nursing communication and supervision, nursing practice guidelines, and task assignment and medical equipment readiness, and 3) Outcomes, including service recipients, service providers, and organization. After implementing the developed system, critical care nursing outcomes showed improvement trends and met the indicators. Professional nurses received competency development and increased participation in specialized critical care nursing training programs. This indicates that the developed nursing service system can effectively and efficiently enhance nursing quality. However, continuous monitoring and supervision of the system should be maintained.